Criminal Liability Against The Criminal Act of Trafficting Children for The Purpose of Prostitution (Study of Decision No. 1.262/Pid. B/2008/PN. Mdn) - Grace Eka Astuti Tamba (Journal of Law Science, 2020)
Trafficking in people for the purpose of prostitution is one of the fastest growing criminal activities in the world. This crime continues to grow nationally and internationally. Although men are also victims of trafficking, the majority of those trafficked are women and children who come from poor families in rural and urban slum areas. The way it works always involves brokers or agents. The brokers and agents are tasked with approaching victims in rural areas, crowds, cafes, and restaurants. Cases of crimes against women and children or trafficking, even though they have been handled, are expected to continue to increase. This condition is influenced by the still weak economic level for some regions and weak law enforcement. This is the reason behind the author's interest in writing a thesis with problems including what regulations are related to child trafficking and how is criminal responsibility for perpetrators of criminal acts of child trafficking for the purpose of prostitution. This thesis is a normative juridical research, by conducting library research and analyzing the decision of the Medan District Court in Case Register No. 1.262/ Pid. B/ 2008/ PN. Mdn.In Indonesia itself, the problem of prostitution is not a new thing. This can be seen from the era of the Javanese kingdoms which was growing during the colonial era. During the Dutch colonial era, the WvS (KUHP) was enacted which was also used by Indonesia. However, the Indonesian government feels that the articles in the Criminal Code cannot ensnare traffickers, then the government seeks a ban on child trafficking which has been stated in various laws and regulations, starting from Law no. 39 of 1999 until the enactment of Law No. 21 of 2007 on the Eradication of the Crime of Trafficking in Persons. Indonesia also participates at the international level, namely by ratifying various conventions, namely the Convention on the Rights of the Child in 1989 and the ILO Convention Number 182 in 1999. Regarding the concept of criminal responsibility for the perpetrators of the crime of trafficking in children for the purpose of prostitution, it is the same as criminal liability in general, namely that there must be errors and the ability to be responsible, where the implementation of the criminal provisions is seen from the tempus delicti.